Appendix to "Consonants in spontaneous speech of five Danish children with operated cleft palate - an impressionistic analysis" - Lowe Nielsen, Connie; Cohn, Wendy; Brøndsted, Kirsten (Annual Report of the Institute of Phonetics University of Copenhagen, 1986)
No abstract